2016
DOI: 10.3390/ijms17071162
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Tunes Hematopoietic Stem/Progenitor Cells for Inflammation and Atherosclerosis

Abstract: As the pathological basis of cardiovascular disease (CVD), atherosclerosis is featured as a chronic inflammation. Hypercholesterolemia is an independent risk factor for CVD. Accumulated studies have shown that hypercholesterolemia is associated with myeloid cell expansion, which stimulates innate and adaptive immune responses, strengthens inflammation, and accelerates atherosclerosis progression. Hematopoietic stem/progenitor cells (HSPC) in bone marrow (BM) expresses a panel of lipoprotein receptors to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…Hypercholesterolemia has multiple effects on HSPCs, including (i) inducing HSPC proliferation and differentiation, (ii) mobilizing HSPCs for release from the bone marrow niche, and (iii) potentiating HSPCs for homing to extramedullary sites, including sites of tissue damage [reviewed in Ref. ( 35 , 36 )]. In rodent models of obesity, Nagareddy et al showed that obesity is associated with both monocytosis and neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia has multiple effects on HSPCs, including (i) inducing HSPC proliferation and differentiation, (ii) mobilizing HSPCs for release from the bone marrow niche, and (iii) potentiating HSPCs for homing to extramedullary sites, including sites of tissue damage [reviewed in Ref. ( 35 , 36 )]. In rodent models of obesity, Nagareddy et al showed that obesity is associated with both monocytosis and neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that aging and increased fat-derived energy intake are risk factors for arteriosclerotic disease, and enhanced oxidative stress and chronic inflammation are considered as the cause of arteriosclerotic disease [ 8 , 9 , 10 , 11 , 58 ]. Chronic inflammation is likely to develop in elderly people, and it was revealed that inflammatory cytokine levels in the blood are high even in healthy individuals [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in fat-derived energy intake has been reported as a possible risk factor for arteriosclerotic disease [ 4 , 5 , 6 , 7 ]. Obesity and glycolipid metabolism disorder induced by this increased fat intake trigger oxidative stress characterized by increased reactive oxygen species and decreased anti-oxidative function as well as inflammatory reaction associated with abnormal secretions of adiponectin and inflammatory cytokines, which leads to the onset of arteriosclerotic disease [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Since preventing the onset and inhibiting the recurrence of arteriosclerotic disease are significant social challenges in Japan—a country with a super-aging society and an increasingly westernized diet—the expectations and efficacy of different functional foods on disease prevention and treatment have been actively studied [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While LDL levels are correlated with circulating HSPCs, no correlation was observed with the white blood cell population. However, subjects in this study were either healthy or had only mild hypercholesterolemia, which may not necessarily lead to the typically observed increase in mature myeloid cells that occurs in familial hypercholesterolemia (FH) patients, who have 2-3-fold higher LDL-C levels (23,93). It appears paradoxical that high LDL-C content activates Srebp2 in circulating HSPCs.…”
Section: Downloaded Frommentioning
confidence: 96%